A Comparison of NCAA FBS Head Coaches Salary Determination From New and Modified Contracts. (June 2021) - Brook, Stacey L.
Previous research examines head football coaches' salary only using aggregate athletic department revenues. Using detailed football program fixed and variable revenues provided in the NCAA Membership Financial Reporting System data, head football coaches signing either new and modified contracts are able to capture both variable and fixed revenues when negotiating salaries. Additionally, for the two other labor groups (student athletes and assistant head coaches), assistant head coaches salary is positive and statistically significant with respect to head coaches' salary, while student athletes aid is statistically insignificant, possibly due to the cap imposed on student athletic aid during this time period.